2009
DOI: 10.1371/journal.pntd.0000514
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Venezuelan Equine Encephalitis Virus from Bolivia, Ecuador and Peru: Identification of a New Subtype ID Lineage

Abstract: Venezuelan equine encephalitis virus (VEEV) has been responsible for hundreds of thousands of human and equine cases of severe disease in the Americas. A passive surveillance study was conducted in Peru, Bolivia and Ecuador to determine the arboviral etiology of febrile illness. Patients with suspected viral-associated, acute, undifferentiated febrile illness of <7 days duration were enrolled in the study and blood samples were obtained from each patient and assayed by virus isolation. Demographic and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…This data is corroborated by a previous study of healthy participants, in which we found that nearly 25% of the urban population carries VEEV-neutralizing antibodies [24]. In addition, based on data collected through this program the geographic range of MAYV and VEEV is wider than had been previously demonstrated, extending to southern Peru and Bolivia [14], [19]. Taken together these factors suggest that the potential establishment of the neotropical alphaviruses as urban pathogens should be closely monitored.…”
Section: Discussionsupporting
confidence: 88%
“…This data is corroborated by a previous study of healthy participants, in which we found that nearly 25% of the urban population carries VEEV-neutralizing antibodies [24]. In addition, based on data collected through this program the geographic range of MAYV and VEEV is wider than had been previously demonstrated, extending to southern Peru and Bolivia [14], [19]. Taken together these factors suggest that the potential establishment of the neotropical alphaviruses as urban pathogens should be closely monitored.…”
Section: Discussionsupporting
confidence: 88%
“…This has already been observed with other arboviral viruses, such as chikungunya, dengue, yellow fever, and Japanese encephalitis viruses [51]. Similar trends have also been observed with enzootic strains of VEEV that have caused endemic disease as well as outbreaks in Peru, Central America, and Mexico [16], [17]. Historically, studies of VEEV emergence have focused on epidemic strains within subtypes IAB and IC; however, enzootic ID and IE strains can also cause a large burden of endemic disease, which can often be misdiagnosed as dengue fever [52].…”
Section: Discussionsupporting
confidence: 78%
“…Surveillance conducted in Cochabamba revealed that VEEV causes a similar number of febrile cases to dengue virus (7 vs 6.6%, respectively, of dengue-like illness) [41], providing evidence that VEE represents a serious public health concern in the area and that its impact has been greatly underestimated. Moreover, an adult Bolivian patient developed neurological disease after infection with this Bolivia/Peru VEEV subtype ID genotype, confirming the severe disease potential of enzootic VEEV from this region [40]. Ecological studies are still needed to identify reservoir hosts and mosquito vectors involved in enzootic transmission in Bolivia, as well as to determine whether VEEV circulates in other areas of the country that are not sampled by current surveillance activities.…”
Section: Vee Complexmentioning
confidence: 95%
“…The circulation of VEEV subtype ID in Bolivia was first reported in 2005, when the virus was isolated from febrile patients residing in Eterazama, Cochabamba [40,41]. Since this initial report, VEEV has been almost continuously isolated in Bolivia from patients with no history of travel within 30 days of their illness, suggesting that VEE is endemic in Bolivia.…”
Section: Vee Complexmentioning
confidence: 99%
See 1 more Smart Citation